(untitled) (Agricultural Engineering, 2016)
The objective of the paper was to assess the usefulness of bark of black locust trunks as an energy source based on chemical and energy properties. Material for research was collected from five forest stands of black locust (Robinia pseudoacacia L.). After determination of the bark mass, its participation in the mass of trees, the content of moisture in bark, density, calorific value, ash, content of C, H, N, S, K and P were established. In comparison to wood, bark has worse chemical properties on account of a high content of sulphur and nitrogen. In the conditions of research, black locust bark had an average density of approx. 400 kg·m−3 which is comparable to the willow and poplar wood. Average calorific value of black locust bark was by 10% higher than the average value of this parameter for bark wood.